Pengaruh Model Pembelajaran Quantum Teaching Learning terhadap Hasil Belajar Siswa Kelas V MI - Girang Awan Satriyo Aji Susanto; Meirza Nanda Faradita; Ishamatun Naila (Journal on Education, 2023)
This research was carried out because there were various problems that were found by researchers including, (1) learning models that were less varied, (2) students were less active in learning unable to voice everyday knowledge in learning, (3) when learning students did not pay attention to what being conveyed by the teacher, (4) students tend to only use memorizing methods without being accompanied by the ability to reason and associate them in everyday life. So that this has an impact on student learning outcomes that are not good. This study aims to see how influential the quantum teaching learning model is on student learning outcomes. This research is a quantitative research with an experimental quasy research design with data analysis steps using t the population used in this study are students of class V MI 25 Surabaya consisting of four classes and taken research samples class V D as an experimental class and class V B as a control class. The data obtained was taken from the test sheet and pre-test conducted by the researcher. from the results of data analysis it was found that learning using the quantum teaching model could improve student learning outcomes in science subjects.